2015
DOI: 10.1016/j.jes.2014.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of Giardia from a full scale MBR sewage treatment plant caused by membrane integrity failure

Abstract: Membrane bioreactors (MBR) are highly efficient at intercepting particles and microbes and have become an important technology for wastewater reclamation. However, many pathogens can accumulate in activated sludge due to the long residence time usually adopted in MBR, and thus may pose health risks when membrane integrity problems occur.This study presents data from a survey on the occurrence of water-borne Giardia pathogens in reclaimed water from a full-scale wastewater treatment plant with MBR experiencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…In treatment plant influents and effluents that have been surveyed, Assemblages A and B, both of which are known to infect humans, were found (Cacciò et al, 2003;Sulaiman et al, 2004;Robertson et al, 2006;Dungeni and Momba, 2010;Khouja et al, 2010;Samie and Ntekele, 2014;Zhang et al, 2015). Taken together, the predominance of Assemblage A was noted.…”
Section: Imsmentioning
confidence: 91%
See 1 more Smart Citation
“…In treatment plant influents and effluents that have been surveyed, Assemblages A and B, both of which are known to infect humans, were found (Cacciò et al, 2003;Sulaiman et al, 2004;Robertson et al, 2006;Dungeni and Momba, 2010;Khouja et al, 2010;Samie and Ntekele, 2014;Zhang et al, 2015). Taken together, the predominance of Assemblage A was noted.…”
Section: Imsmentioning
confidence: 91%
“…In Brazil, cysts were detected at concentrations as high as 10 5 cyst/L (Neto et al, 2006;Hachich et al, 2013). In contrast, relatively few studies have reported cysts at concentrations not exceeding 100 cysts/L (Reinoso et al, 2011;Yapo et al, 2014;Zhang et al, 2015). These data underscore the variability in cyst concentration in influent samples, which is likely influenced by the source of wastewater (e.g.…”
Section: Raw Sewage and Sludgementioning
confidence: 93%
“…Wastewater was another common focus of risk assessment in LMIC, covering wastewater irrigation [30, 51, 52, 66, 67, 7173, 174], livestock waste [53, 68], non-potable reuse or greywater [44, 175], treatment failure [49], and effluent discharge [50]. The pathogens of interest were varied and included E. coli (N=5), Giardia (N=4), Salmonella (N=3), rotavirus (N=3), and Cryptosporidium (N=3).…”
Section: Pathways and Pathogens: Research Priorities In Lmic And Hic mentioning
confidence: 99%
“…G. lamblia, G. intestinalis ), un protozoario enteropatógeno ubicuo que causa la enfermedad diarreica aguda y la gastroenteritis en humanos y sobre todo en niños (1, 2). El parásito puede transmitirse a través del agua tratada debido a su resistencia a los agentes de inactivación (3, 4), así como de los alimentos contaminados, de persona a persona o de animal a persona por vía fecal-oral (4, 5). La infección puede ser asintomática o manifestarse como diarrea persistente y síndrome de malabsorción (6) y, en casos crónicos, producir retraso en el crecimiento y en el desarrollo cognitivo infantil (7).…”
unclassified